IMPLEMENTATION OF THE MAUT METHOD ASSESSMENT OF THE BEST SALESPERSON - Reza Fadillah Reza Fadillah; Risnawati; Sudarmin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Arif Jaya Stores is a company engaged in sales. Every day, Arif Jaya Stores serves about 1-30 sales transactions and has 25 salespeople. The system used by the Arif Jaya Store is still manual, namely the recording system in the book in searching for data so that it has difficulty. Likewise, the process of evaluating the performance of sales clerks still uses an observation system, which of course takes a long time and the assessment becomes less objective, because it is not based on the proper calculation of criteria. The purpose of this study is to facilitate the implementation of the MAUT method based on criteria and alternatives in making decisions about the best sales assistant at Arif Jaya Air Joman Stores. This research method is carried out by applying decision support system techniques and using the MAUT method. Data testing is done using manual calculations using Microsoft Excel and will be implemented into the VB.NET programming language with MySQL as the database. So the results of this study are that what is worthy of being recommended as the Best Sales Assistant is the 9th alternative on behalf of Lili Fadilla with a total value of 0.9.